EVALUASI STRATEGI BAURAN PROMOSI (PROMOTION MIX)PRODUK AIR MINUM DALAM KEMASAN PADA PERUSAHAAN PT ATLANTIC BIRURAYA - Melliyana Melliyana; Dudi Anandya; Indarini Indarini (Perpustakaan Universitas Surabaya, 2018)
This internship report activity is conducted to know and evaluate the implementation of Promotion Mix Strategy on bottled mineral water product of PT Atlantic Biruraya in Surabaya. In conducting promotional activities, the company using variety of promotional strategiesto attract customers with company’s product. This internship report activity was conducted for 316 hours and the participant performed the role asa marketing team that helps the process of digital marketing and personal selling. With concept of Marketing Mix Strategy and Sales Management, the participant can evaluate Promotion Mix Strategy on bottled mineral water product of PT Atlantic Biruraya. During the internship, found some obstacles in the process of promotion mix strategy. Therefore, PT Atlantic Biruraya, especially marketing team still needs to make improvements to promote the company better and attract customers and potential customers.